2023
DOI: 10.1002/cssc.202300907
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Functional Organofluoride Catalysts for Polyesters Production and Upcycling Degradation

Qiao Zhang,
Chenyang Hu,
Xuan Pang
et al.

Abstract: The production and degradation of polyesters are two crucial processes in polyester materials’life cycle. In this work, multi‐functional organocatalysts based on fluorides for both processes are described. Organofluorides were developed as catalysts for ring‐opening polymerization of lactide (lactone). Compared with a series of organohalides, organofluoride performed the best catalytic reactivity because of the hydrogen bond interaction between F– and alcohol initiator. The Mn values of polyester products coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…During the past decade, several metal-based catalysts have been documented, predominantly Zn-based complexes. Other metals including Mg, , Ca, Sn, and Bi have also been investigated. Metal-free catalytic conditions have also been explored. Our team has reported that sodium l -ascorbate and organofluorides can catalyze both ring-opening polymerization of lactide to PLA and the alcoholysis of PLA. , However, considering part of the industrial applications, catalyst removal and recycling from the organic products are essential but increase production costs. Therefore, we investigated the possibility of designing a novel catalyst-free process for polymer degradation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, several metal-based catalysts have been documented, predominantly Zn-based complexes. Other metals including Mg, , Ca, Sn, and Bi have also been investigated. Metal-free catalytic conditions have also been explored. Our team has reported that sodium l -ascorbate and organofluorides can catalyze both ring-opening polymerization of lactide to PLA and the alcoholysis of PLA. , However, considering part of the industrial applications, catalyst removal and recycling from the organic products are essential but increase production costs. Therefore, we investigated the possibility of designing a novel catalyst-free process for polymer degradation.…”
mentioning
confidence: 99%
“…Based on the literature, ,,,,,,, a mechanism for the depolymerization is proposed in Scheme . Due to the high polarity and the uneven electronic density contribution, the DMF molecule could be regarded as a “δ + δ – ” Lewis pair .…”
mentioning
confidence: 99%